Foreign exchange market in the Republic of Serbia: a comparative analysis with selected countries - Dimić, Maja; Cvijović, Jelena; Ćosić, Milica (Industrija, 2024)
The primary purpose of the foreign exchange market is to facilitate and enhance international trade and capital movement, while also ensuring the smooth execution of payment transactions and maintaining liquidity within the economy. A well-functioning foreign exchange market contributes to the interconnectedness of national financial markets and serves as a crucial link between national economies and the international environment. This paper analyzes the foreign exchange markets of Serbia, Romania, and Hungary within the context of the global economic crisis and the COVID-19 pandemic. The objective of the research is to compare the effects of these crises on exchange rates and the stability of financial markets in the countries. The authors illustrate the mechanisms through which global economic shocks have impacted foreign exchange markets, as well as the responses of governments and central banks to the challenges posed by these crises. Furthermore, this paper contributes to the understanding of the dynamics of foreign exchange markets during times of crisis and provides insights into strategies that have proven successful in preserving economic stability, thereby opening avenues for further research in this domain.